Simulation model of Prostephanus truncatus (Coleoptera: Bostrichidae) in rural maize stores in the Republic of Benin - Meikle, W.G.; Holst, N.; Scholz, D.; Markham, R.H. (1998)
. A distributed-delay, demographic simulation model of Prostephanus tnmcatus (Horn) populations in rural maize (Zea mays L.) stores was developed and validated. Developmental and mortality parameters for eggs, larvae, and pupae, and the life span and fecundity data for adult insects, were estimated from published data and from laboratory experiments. The overall phenology of the simulated beetle dynamics reflected that of field data, although the model output tended to overestimate beetle population growth during the season and overall density late in the season. The model was developed as part of a low-cost tool for evaluating the major factors influencing population dynamics of stored-product pests and their natural enemies and to provide a conceptual framework for evaluating different control strategies in an integrated control context.